Biomechanical analysis of snowboarding from field load acquisitions - Petrone, N. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
Snowboarding is becoming more and more popular and safety issues as well as technical development are strategic for users, trainers and manufacturers. Despite the publication of safety standards, very few data are available to author`s knowledge about loads applied to the bindings of a snowboard during slalom and half-pipe manoeuvres, as well as during falls: furthermore, these are usually property of few boards or bindings manufacturers. The knowledge of loads at the bindings is fundamental for any engineering design of boards and bindings as well as for modelling the athlete`s biomechanics as needed in analysing the sport technique or in developing protective devices. Methods: A couple of dynamometric platforms was designed to record binding loads from snowfield manoeuvres: the platforms, suitable for both soft and hard boots, were designed in accordance with geometric, stiffness and sensitivity requirements, allowing for the acquisition of six force and moment components at each foot [1]. Each platform consists of an aluminium plate applied to the snowboard with usual bolts for canting adjustment, so that functional specifications remained unaltered. Each platform was calibrated on a rigid board fixed on a test-bench and loaded by known forces and moments. A complete test campaign was performed considering typical manoeuvres in slalom, free-style and free-ride as well as particular events in half-pipe and jumps. Different athletes performed standard runs and manoeuvres to enable comparative analyses. Results: Data collected from the bindings in terms of nominal loads at the binding were analysed and reported in the board`s reference frame. This allowed to understand the athlete`s motion in the slope and to validate models of the slalom or the jump event. Moreover, loads from the binding can be resolved to the ankle and knee joints in order to give again information for biomechanical models of the limbs and comparisons with safety standard requirements. Discussion: The analysis of collected data allowed to estimate maximum loads and load spectra, as well as correlations between athletes technique in back-side and front-side curves and sport performance. The system was used with a portable data logger in a backpack, but it can allow for even wider applications after adoption of a pocket PDA acquisition system and combination with a set of physiological and EMG sensors. Functional evaluation, technical optimisation and quantitative training are possible with the developed system after telemetry recording of the boarding technique of elite and junior athletes.